Studi Mikrobiologi pada Jajanan Kaki Lima di Sekolah Dasar Kecamatan Tarakan Barat: Implikasi bagi Keamanan Pangan - Sholehah, Nur Ulya Aufa; Rukaya, Benazir Evita; Syuhada, Syuhada (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to evaluate the microbiological safety of street food sold by vendors in Tarakan Barat District. The evaluation was conducted on 12 food samples, consisting of 8 types of food and 4 types of beverages, randomly collected from vendors in four sub-districts: Karang Anyar, Karang Balik, Karang Rejo, and Karang Anyar Pantai. Samples were tested using the Total Plate Count (ALT) method to determine the bacterial colony count in the tested food and beverages. The results showed that (1) the sample with the highest contamination level among food items was Pentol Rebus/Kukus (3,19 Ã— 10Â¹â°CFU/g), while the beverage with the highest ALT was Es Teh Sisri (I) (2,59 Ã— 10Â¹â° CFU/ml) obtained from SDN 003 Tarakan, whereas Es Teh Sisri (D) from SDN 1 Utama Tarakan showed a TFTC (Too Few to Count) result; (2) The high microbial contamination levels in these street foods are suspected to be caused by several factors, including poor environmental sanitation, lack of vendor hygiene, and exposure to dust and pollution from the selling locations. Most of the tested samples had ALT levels far exceeding the limits set by BPOM, confirming that street food poses a risk of causing various diseases such as gastrointestinal infections, diarrhea, food poisoning, and typhoid fever, which may negatively impact the health of elementary school students in Tarakan Barat District.